KAJIAN KERENTANAN MASYARAKAT DALAM PENGELOLAAN DARATAN WILAYAH PESISIR KOTA KUPANG TERHADAP ANCAMAN GELOMBANG TINGGI - Wibowo, Tri U.; Kotta, Herry Z.; Effendi, Jauhari (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
Kupang City is the capital of East Nusa Tenggara Province located in Kupang Bay, based on historical data has encountered several of the earthquake that caused high tide. This study aims to obtain vulnerability of coastal society in land management of Kupang City coastal through those natural disasters, this study covers 15 villages located along the coast of Kupang City. Determination of the vulnerability using spatial analysis with GIS software Quantum Valmiera 2.2 and ArcGIS 9.3 , descriptive statistics, scoring systems and weighting limitation vulnerable areas under 10.5 meters above sea level, which is an overlay be physical vulnerability map. Physical vulnerability variable such as structured area, and the density of buildings.Non-physical vulnerability variable such economic area parameters, livelihoods, and population density. Environmental vulnerability variable parameters such as elevation, distance from the shoreline and coastal protection forest .There are three levels of vulnerability; high, medium, and low. From the resulting overlay of each variable and parameters obtained the vulnerability of coastal areas in Kupang City was dominated by the 9 villages with medium vulnerability, 1 village with high vulnerability, and there are no villages in the low vulnerability. 5 villages are safe from high tides.